Antimicrobial susceptibility of Acinetobacter isolates from Groote Schuur Hospital region : an investigation of the appropriateness/validity of the NCCLS zone size criteria - Ben-Ismaeil, B I (Division of Medical Microbiology, 2017)
Since the 1970s, relatively uncommon species of non-enteric gram-negative bacilli have emerged as nosocomial colonizers and pathogens. Among them, one of the most significant genera is Acinetobacter, which has given rise to an increasing number of reports of nosocomial infections. The introduction of new broad-spectrum antimicrobials in the hospitals has been one of the main factors responsible for this development.In addition leading to a move from more susceptible towards more resistant pathogens. This occurred both between and within genera. Owing to the unpredictable antimicrobial susceptibility of Acinetobacter spp., it is prudent to test each isolate for its susceptibility profile to guide in the proper treatment of infections caused by Acinetobacter.The disk diffusion method is the technique most widely used by microbiology laboratories for the routine assessment of antimicrobial susceptibility patterns.The zone diameters obtained by this technique for individual antimicrobials are reported as susceptible, intermediate or resistant by referring to an interpretative chart.Most laboratories use interpretative charts (zone size criteria) supplied by the National Committee for Clinical Laboratory Standards (NCCLS) for this purpose.In our laboratory we have noted discrepancies between sensitivities as determined by the NCCLS zone size criteria and the local minimum inhibitory concentration (MIC) results obtained for Acinetobacter species, especially for cefepime (CPIM) and ceftazidime (CT AZ). Since Acinetobacter species contribute significantly to the increased morbidity and mortality of debilitated patients ( especially v entilated ICU patients, and the fact that clinicians rely on the antimicrobial susceptibility results in the management and treatment of these patients, it was felt necessary to investigate the appropriateness/validity of the NCCLS zone size criteria used to interpret the susceptibility test results of cefepime (CPIM), ceftazidime (CT AZ), trimethoprim-sulfamethoxazole (TMP-SULF A), and piperacillin-tazobactam (PIP-T AZO) against Acinetobacter spp.